1968
DOI: 10.2135/cropsci1968.0011183x000800050015x
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis for Grain Yield and Leaf Area and Their Components in Two‐ ✕ Six‐Rowed Barley Crosses1

Abstract: Twelve hybrids between two‐ and six‐rowed barley varieties were evaluated for heterosis for two complex traits through the component interaction approach. On the average, very low levels of heterosis were found for the complex traits (grain yield per plant and total leaf blade area per plant). Data were presented on some of the possible causes of the failure of component niteraction to produce heteroic effects for the complex trait. The negative association of kernels per head and weight per kernel and the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They concluded that yield heterosis is not only expressed at low seeding rates, but that it can result from contributions from different yield components in different environments. Carleton and Foote (1968) did not find heterosisi for yield or for leaf area in tworow by six-row crosses, even though the parents differed reciprocally for components of yield and for components of leaf area. Upadhyaya and Rasmusson (1967) also found some hybrids that exhibited no heterosis for yield, even though the parents differed reciprocally for the components of yield.…”
Section: Base Of Heterosis In Barleymentioning
confidence: 58%
“…They concluded that yield heterosis is not only expressed at low seeding rates, but that it can result from contributions from different yield components in different environments. Carleton and Foote (1968) did not find heterosisi for yield or for leaf area in tworow by six-row crosses, even though the parents differed reciprocally for components of yield and for components of leaf area. Upadhyaya and Rasmusson (1967) also found some hybrids that exhibited no heterosis for yield, even though the parents differed reciprocally for the components of yield.…”
Section: Base Of Heterosis In Barleymentioning
confidence: 58%
“…The increasing effect of heterozygosity with increasing levels of stress confirms the observations of Finlay (1964) for grain yield of barley. Carleton and Foote (1968) observed no heterosis in crosses between two-rowed and six-rowed barley. They argued that the growing conditions in their glasshouse experiment might have been too close to optimum to exhibit heterosis.…”
Section: Discussionmentioning
confidence: 77%
“…Heterosis varies in degree, and may be shown by various plant attributes, such as size, tillering capacity or grain size [24,25]. The value of this approach is not universally accepted, since 'hybrid vigour' should be 'fixable' in homozygous plants.…”
Section: 'Hybrid' Barleymentioning
confidence: 99%